Вплив манітолу на індукцію та регенерацію морфогенної калусної тканини у кукурудзи - Абраімова, О.Є.; Деркач, К.В.; Сатарова, Т.М.; Шевченко, Н.В.; Черноусова, Н.М. (Фактори експериментальної еволюції організмів, 2015)
Aims. In maize (Zea mays L.) callusogenesis on immature embryos is the basis for obtaining somaclones, cell selection,
genetic engineering. The aim of the study was to examine the effect of mannitol in an induction medium on obtaining and
regeneration capacity of morphogenic calli. Methods. Plant tissue culture method for assessing morphogenetic reaction of
9 maize lines was used. Results. Mannitol significantly increased frequencies of morphogenic calli induction, reduced their
differentiation, but inhibited fresh weight accumulation. Calli obtained on the mannitol contained medium had improved
regeneration ability. Conclusions. Mannitol is an effective component for the induction of morphogenic calli of different
types and for maintenance of regeneration ability of callus tissue of type I.
Keywords: mannitol, maize, culture in vitro, morphogenic callus, regenerants.